Argentina : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Argentina's investment rate which was well below the average of Latin American countries and that of a peer group of advanced and emerging market countries, with a larger gap in private investment. Raising investment prospects would be essential to boost economic activity. The administration that took office in December 2015 has emphasized the importance of generating an investor friendly environment that allows Argentina to recover some of the growth opportunities lost over the last few decades. Although quantifying the capital accumulation gap is a clearly a difficult task, one way of doing so is to look at the difference between Argentina's capital-labor ratio and that of the selected peer group of countries. Argentina's investment rates and capital-output ratios are also compared with estimates of their steady state values derived from standard neoclassical growth models. Argentina's investment rate would need to increase significantly to eliminate the capital accumulation gap built during the last two decades, and this could significantly accelerate GDP growth.